PENGUJIAN BLACK BOX PADA WEBSITE BUITENZORG OUTDOOR MENGGUNAKAN METODE USE CASE TESTING DAN BOUNDARY VALUE - Jovita Nabilah Azizi; Ester Olivia Silalahi; Rafli Damara; Muhammad Farhan Fahrezy; Fikri Saputra; Aditya Wicaksono; Muhammad Nasir (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) - Institut Teknologi dan Bisnis Semarang, 2024)
Software testing is a critical aspect of application development to ensure quality and functionality. This research focuses on black box testing of the Buitenzorg Outdoor website, a platform for renting outdoor equipment. Using the Use Case Testing and Boundary Value methods, this study aims to identify the reliability of functionalities based on user scenarios and input/output validation. The methodology involves use case analysis to define key testing scenarios and boundary value analysis for critical features. The results indicate that several website modules have defects in input validation, particularly in the booking and user registration forms. Based on the testing results, the system performed well with a success rate of 98.64%. This study contributes to improving web-based system testing processes through a systematic and replicable approach. The findings also highlight the importance of use case-based testing to mitigate functional risks in real-world usage environments.